Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1995
DOI: 10.2527/1995.731128x
|View full text |Cite
|
Sign up to set email alerts
|

In vivo study of circadian variations of the cecal fermentation pattern in postweaned and adult rabbits.

Abstract: Two groups of cecal cannulated rabbits (postweaned and adult, 6 and 16 wk of age, respectively) were used to compare the circadian variations of the fermentation pattern. Rabbits were kept in metabolism cages under a 12:12 light-dark schedule (0700 to 1900). For each rabbit, a total of 12 samples of cecal material were collected (every 12 h) for six consecutive days to cover a 24-h cycle; feed ingestion and hard feces elimination were recorded. For postweaned and adult rabbits, the period of cecotrophy practic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
45
2
1

Year Published

1996
1996
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 20 publications
12
45
2
1
Order By: Relevance
“…In conformity with the data of the literature (Bellier et al, 1995;Padilha et al, 1995;, the proportion of propionic acid (C3) was higher than that of butyric acid (C4) before weaning, but thereafter this became reversed, so that the ratio of the two fatty acids (C3 : C4) decreased from .1.0 to ,1.0. The increase of the butyrate concentration might be explained by an increase in some butyrate-producing bacteria.…”
Section: Discussionsupporting
confidence: 89%
“…In conformity with the data of the literature (Bellier et al, 1995;Padilha et al, 1995;, the proportion of propionic acid (C3) was higher than that of butyric acid (C4) before weaning, but thereafter this became reversed, so that the ratio of the two fatty acids (C3 : C4) decreased from .1.0 to ,1.0. The increase of the butyrate concentration might be explained by an increase in some butyrate-producing bacteria.…”
Section: Discussionsupporting
confidence: 89%
“…However, Maertens and Peeters (1988) or Taranto et al (2003) observed a higher pH and a lower VFA concentration in the caecum of young restricted rabbits, since measurements were performed in the morning (9-10 h) just after meal distribution and thus before the peak of digestion in the caecum. In contrast, the fermentative activity of ad libitum-fed rabbits is relatively stable over the nycthemere (Bellier et al, 1995), thus explaining their relatively lower VFA concentration of the AL group. Irrespective of the restriction level, the xylanasic and pectinasic activity of caecal bacteria was higher than that of the cellulase.…”
Section: Discussionmentioning
confidence: 66%
“…Inversely, the total VFA concentration was lower than that mentioned by Padilha et al [18] (30-35 mmol-L-1 ) using SPF (but weaned) rabbits, or that observed in conventional weaned rabbits (50-80 mmol-L-1 ) [2,16,19,20]. The [20] and in vivo [16].…”
mentioning
confidence: 71%